Pengaruh Jenis Cairan Pelapis terhadap Tingkat Pencoklatan Buah Apel dengan Rancangan Acak Kelompok Lengkap - Panjaitan, Hotnauli Roni Arta; Triana, Dinie; Hutapea, Risca Octaviyani; Pulungan, Zakiy Maulana; Ndruru, Albert Servant (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to determine the effect of coating solutions consisting of control, lemon water, and salt water on the browning intensity of fresh-cut apples using a Completely Randomized Design (CRD). Enzymatic browning is a major problem in fresh-cut apples due to the oxidation of phenolic compounds triggered by the activity of the polyphenol oxidase enzyme. Lemon water acts through mechanisms of pH reduction and antioxidant activity, while salt water inhibits browning through ionic effects and osmotic pressure. The experiment was conducted using homogeneous apple units, and the browning scores obtained were analyzed using ANOVA at a 5% significance level. The results showed a significant effect among treatments, with an F-value of 5.136 exceeding the F-table value of 4.226. Lemon water was found to be the most effective in inhibiting browning, followed by salt water, while the control treatment exhibited the highest browning intensity. These findings confirm that simple natural materials can serve as effective anti-browning coatings, especially when applied to homogeneous experimental units using a CRD.